2010
DOI: 10.1186/1742-2094-7-30
|View full text |Cite
|
Sign up to set email alerts
|

Dimethylfumarate inhibits microglial and astrocytic inflammation by suppressing the synthesis of nitric oxide, IL-1β, TNF-α and IL-6 in an in-vitro model of brain inflammation

Abstract: BackgroundBrain inflammation plays a central role in multiple sclerosis (MS). Dimethylfumarate (DMF), the main ingredient of an oral formulation of fumaric acid esters with proven therapeutic efficacy in psoriasis, has recently been found to ameliorate the course of relapsing-remitting MS. Glial cells are the effector cells of neuroinflammation; however, little is known of the effect of DMF on microglia and astrocytes. The purpose of this study was to use an established in vitro model of brain inflammation to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
217
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 313 publications
(236 citation statements)
references
References 42 publications
16
217
2
1
Order By: Relevance
“…Consistent with previously published reports,6, 11, 13, 30 our data demonstrate that fumarates significantly reduce inflammatory cytokine and chemokine secretion in response to proinflammatory stimuli. We further demonstrate that the reduction in cytokine and chemokine production by fumarates within astrocytes is limited to DMF, as MMF had no significant effect on cytokine and chemokine secretion.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Consistent with previously published reports,6, 11, 13, 30 our data demonstrate that fumarates significantly reduce inflammatory cytokine and chemokine secretion in response to proinflammatory stimuli. We further demonstrate that the reduction in cytokine and chemokine production by fumarates within astrocytes is limited to DMF, as MMF had no significant effect on cytokine and chemokine secretion.…”
Section: Discussionsupporting
confidence: 93%
“…The recruitment of inflammatory cells and modulation of the local inflammatory milieu implicate the astrocyte as an important regulator of neuroinflammation 18. As such, DMTs capable of influencing astrocyte activation may be beneficial in the context of MS. DMF has previously been demonstrated to reduce the activation of astrocytes, highlighting multiple potential mechanisms through which DMF may reduce neuroinflammation 11, 13. Although these studies demonstrated an effect of DMF in vitro, differential effects of MMF and DMF, as well as any potential species effects between humans and mice have not been investigated to date.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…It has been shown that Nrf2, a relative of Bach 1, inhibits the maturation of DCs in vitro 42 and protects humans from MS development. 25,26 Potentially, Nrf2 and Bach1 might serve as counterparts in the CNC/Maf regulatory network, regulating the homeostatic balance of DC development and MS pathogenesis. Moreover, it is important to highlight that deletion of Bach1 did not completely ablate APC development, suggesting that other CNC and/or small Maf subunits might have compensatory or redundant functions with Bach1.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the fumaric acid ester dimethylfumarate, which exerts neuroprotection by inducing Nrf2 expression, is currently in a phase 3 clinical trial as an orally active effective treatment of human multiple sclerosis with limited side effects. 25,26 Thus, deciphering the functions of the individual CNC subunits will not only be crucial to unraveling the overlapping and unique functions of these proteins but also provide insights to the potential of targeting CNC proteins for therapy against relevant diseases. In particular, the CNC member Bach1 is up-regulated in fetal Down syndrome (DS) brain.…”
mentioning
confidence: 99%